Extraction and quantification of exchangeable aluminum in Fibric Histosol - Campos, José Ricardo da Rocha; Silva, Alexandre Christófaro; Silva, Enilson de Barros; Vidal-Torrado, Pablo (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate different methods for extraction and quantification of exchangeable aluminum in Fibric Histosol. Samples were collected in three peat bog profiles and then air dried and passed through 2 mm sieve. Extractions were made with KCl 1 mol L-1, Ca(OAc2) 1 mol L-1, and CuCl2 0.5 mol L-1. Then, the extracts obtained by KCl and Ca(OAc2) were analyzed by titration with NaOH 0.025 mol L-1 and by graphite furnace atomic absorption spectrometry (GF‑AAS). The extracts obtained by CuCl2 were analyzed by GF‑AAS. Quantifying with GF‑AAS resulted in similar ability of KCl and Ca(OAc2) to extract exchangeable aluminum, whereas CuCl2 was also able to extract the reactive Al. The high levels of exchangeable aluminum observed in titration after extraction by KCl may be related to the high levels of the H+ ion present in the samples. The method recommended for determination of exchangeable aluminum content in Fibric Histosol is extraction with KCl or Ca(OAc2) and, for quantification, the graphite furnace atomic absorption spectrometry.